Co-modification of lignocellulosic biomass by maleic anhydride and ferric hydroxide for the highly efficient biosorption of methylene blue. (5th October 2021) - Gao, Youcheng; Zeng, Jun; Zhu, Siming; Liu, Qiang
Abstract : Ferric hydroxide and microwave-assisted solvent-free esterification was applied in the modification of SBP to synthesize an efficient cationic dye adsorbent. Abstract : Herein, a novel biosorbent originated from sugar beet pulp (SBP) was synthesized by microwave-assisted esterification with maleic anhydride (MA) and further decorated with ferric hydroxide. Characterization methods including FT-IR, SEM, XRD, Zeta potential, BET, TG and XPS were used to determine anticipative modification of SBP. The co-modified product of SBP (FMSBP) was applied for the cationic methylene blue (MB) dye removal and the optimization of experimental parameters such as biosorbent dosage, initial pH, contact time, initial MB concentration and temperature were investigated. Biosorption equilibrium followed the Langmuir isotherm model with a theoretical maximum biosorption capacity of 641.3 mg g −1 and the pseudo-second-order kinetic model was more suitable to describe kinetic data, while thermodynamic calculations indicated a spontaneous and exothermic biosorption process. Surface complexation and electrostatic interactions were involved in biosorption mechanisms, and the superior biosorption performance of FMSBP was achieved within 150 min at pH 8. Furthermore, FMSBP was demonstrated for the successful application in simulated real wastewater treatment, and the removal efficiency of MB remained above 70% after six desorption-resorption cycles, indicating a stable and promising biosorbent for decontamination of wastewater containing cationic dye.